Analisis Finansial Deepining Terhadap Pertumbuhan Ekonomi di Indonesia - Ramadanti, Annida; Rendi Putra, Muhammad; Yurillita, Resti; Panorama, Maya (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2022)
This paper aims to analize the financial deepening on Indonesia economy. The focusof analysize is to identifiying effect of interest rate, exchange rate and Gross DomesticProduct (GDP) to financial deepening on Indonesian economy for 1980-2007. Methodeof analysize is linier regression model. The result of analysize is Gross DomesticProduct (GDP) and interest rate have significant effect to financial deepening on Indonesian economy.